Tracing ‘paper', discovering people: three ethnographic case studies exploring the use of health information to improve health services in Gugulethu - Van, Pinxteren Myrna (Department of Public Health and Family Medicine, 2020)
Health information plays a vital role in the larger health system. Over the last twenty-five years, South Africa has developed several health information systems (HISs) that aim to collect high-quality health information to be used to inform clinical decision-making, shape new policies and programmes and strengthen other components of the health system. To date, most research in this area has focused on the production of health information and the technical challenges that appear when developing and implementing HISs. Much less is known about how health information is used in practice. This research explores how both community actors and health systems stakeholders at different levels of the health system gain access to, use and exchange health information, both for their own decisionmaking and practice, but also to address persistent health challenges. This research adopted an ethnographic approach, whereby I conducted extensive qualitative research for a period of 18 months in Gugulethu, an underprivileged peri-urban neighbourhood in Cape Town. Three case studies emerged from this research that provide a lens to analysing the role of health information in South Africa. The use and exchange of health information in the larger health system is inherently complex. Key findings from this research project show that firstly, there is a wide interest among a diverse group of stakeholders, including community representatives and NGOs, to use health information. Secondly, despite the interest for using health information, this data is not always available for a variety of reasons, which encourages stakeholders to develop creative strategies to collect new forms of evidence or to gain access to existing forms of data. Thirdly, adopting new strategies, health actors use a combination of routinely collected, semi-formal, and informal data, often concurrently. Lastly, this research demonstrates that health information is never neutral or value-free, but is produced, used and exchanged within a larger social, cultural and religious context, and is thus shaped by these contexts. This research challenges several assumptions about how health information is used in South Africa, and who can, or should, have access to this information. To answer these questions, it is important to open the health information system (HIS) to a more a diverse group of people actively in order to make available a variety of information that informs health stakeholders' daily work, influences health programmes and provides new perspectives on current health issues. Lastly, to further stimulate the use and exchange of health information for health system strengthening purposes, there is a need to provide a dedicated third space, where establishing new relationships and strengthening existing ones among actors at different levels of the health system is actively encouraged as a way to stimulate further use and sharing of health information.